2008
DOI: 10.1080/11263500701872283
|View full text |Cite
|
Sign up to set email alerts
|

Relations between western Balkan endemicCampanulaL. (Campanulaceae) lineages: Evidence from chloroplast DNA

Abstract: The relationships among western Balkan and some amphi-Adriatic endemic campanulas were studied using RFLP analysis of the 1.8-kb trnT -trnF chloroplast DNA region. The results were compared to those of a comparative floral morphometry study performed earlier on a similar sample. Maximum parsimony and distance methods produced very similar results to those of the floral morphometry, both of which point to a clear separation of the taxa into three main clades. The first isophyllous, or Garganicae series, clade c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…average polymorphism (P) ¼ 0.52, average number of alleles per locus (A) ¼ 1.74, and Nei's gene diversity (H) ¼ 0.19, are higher than those typical for endemic and narrowly distributed taxa (Loveless & Hamrick 1988;Hamrick & Godt 1989;Dejoode & Wendel 1992;Frèville et al 1998;Palermo et al 2002). Potential explanations for the higher than expected levels of diversity includes evolutionary origin, population size and mating system (Neel & Ellstrand 2003;Liber et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…average polymorphism (P) ¼ 0.52, average number of alleles per locus (A) ¼ 1.74, and Nei's gene diversity (H) ¼ 0.19, are higher than those typical for endemic and narrowly distributed taxa (Loveless & Hamrick 1988;Hamrick & Godt 1989;Dejoode & Wendel 1992;Frèville et al 1998;Palermo et al 2002). Potential explanations for the higher than expected levels of diversity includes evolutionary origin, population size and mating system (Neel & Ellstrand 2003;Liber et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…1). Although previously defined as a part of the Isophylla group (Damboldt 1965), recent phylogenetic studies based on plastid and ITS sequences (Park et al 2006;Liber et al 2008;Frajman and Schneeweiss 2009;Bogdanović et al 2014) have rejected the monophyly of the Isophylla group and revealed three well supported clades corresponding to series Elatines Trin., ser. Fragiles Trinajstić, and ser.…”
mentioning
confidence: 99%
“…Results of our analyses suggest that Campanula tommasiniana is a chasmophyte of open and exposed habitats in the altimontane to subalpine vegetation belt, a similar niche preference (see HORVAT 1931) also for the closely related (see PARK et al 2006, LIBER et al 2008) but allopatric C. waldsteiniana, another endemic of the north-western Dinaric Alps.…”
Section: Syntaxonomy Nomenclature and Typification Of The Syntaxamentioning
confidence: 80%